Ketidaksiapan Pasar Tenaga Kerja dalam Menghadapi Era Ekonomi Digital di Indonesia - Kardina Siregar; Lia Nazliana Nasution; Bakhtiar Efendi (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study was conducted in Indonesia with the aim of determining the unpreparedness of the labor market in facing the digitalization era using the Vector Auto Regression (VAR) analysis method with a time series study for 19 (Nineteen) years. There are five variables used, namely e-commerce, economic growth, inflation, unemployment and labor with data obtained from the World Bank. The results of the VAR analysis using the lag 2 basis, the vector autoregression analysis shows the contribution of each variable to the variable itself and other variables. In addition, the results of the vector autoregression analysis also show that the past variable (t-1) contributes to the current variable both to the variable itself and to other variables. The results of the analysis show that there is a reciprocal relationship between the variables. The Response Function Analysis shows whether there are other variables that respond to changes in one variable in the short, medium, or long term. In addition, it is known that the stability of all variables appears for five years or the medium and long term. Variable Decomposition Analysis shows that variables such as ECO, INF, and GDP make the greatest contribution to the variable itself both in the short, medium and long term. In contrast, PG and TK are the other variables that have the greatest influence on the variable itself, with ECO and INF being the most influenced.